Social context affects tissue-specific copper distribution and behaviour of threespine stickleback (Gasterosteus aculeatus) - Sienna L. Overduin; Shaun S. Killen; Alex M. Zimmer; Jenelle D. McCuaig; Lucy Cotgrove; Isabel Aragao; Kelly J. Rozanitis; Kurt O. Konhauser; Daniel S. Alessi; Tamzin A. Blewett (Ecotoxicology and Environmental Safety)
Many species exhibit social living which offers ecological advantages such as increased foraging opportunities, more efficient locomotion and reduced predation risk. Additionally, exposure to multiple individuals of the same species can decrease an individual’s stress and metabolic demand, termed social buffering. If disruption to an animal’s social structure occurs and prevents social buffering, an elevated metabolic rate and thus ventilation frequency and gill permeability are likely. A potential consequence of this physiological response could be the increased accumulation of toxicants. The objective of this study was to investigate whether inducing social stress in marine threespine stickleback (Gasterosteus aculeatus) through social isolation during a sublethal water-borne copper (Cu) exposure would affect Cu uptake and whether that would translate to differences in behaviour and biochemical functioning. We hypothesized that isolating threespine stickleback during a Cu exposure would increase Cu uptake and sublethal toxicity compared to a grouped exposure. Wild-caught fish were exposed to control, low Cu or high Cu conditions (0 – 150 µg/L of Cu, nominally), either in isolation or groups of six for 96 h. Isolated stickleback travelled three times less distance, took six times longer to consume food and exhibited moderately increased gill sodium-potassium ATPase activity than group exposed fish, with no effect of Cu. Isolated stickleback also demonstrated significantly higher Cu levels in their gill and liver tissue compared to the group exposed fish. However, this Cu distribution was also present within the control fish, which had not been exposed to Cu, suggesting that the social context affects endogenous Cu distribution under stressful conditions. Our results illustrate the differences in physiology and behaviour that can arise when social contexts are manipulated and stress the importance of considering sociality when conducting toxicity tests with social organisms.